REVIEW JURNAL THE INFLUENCE OF LEADERSHIP STYLE ON ORGANIZATIONAL CULTURE AT SMA NEGERI 3 MUARO JAMBI - Mutiara Silvia Saripah; Syaiful Anwar; Adinda Putri Azizah; Syakira Utaminingsih; Wulan Hikmah Ratnasari (CV. Four Son Scholarship, 2024)
The purpose of this research is to examine the potential impact of the principal’s leadership style on organizational culture at SMA Negeri 3 Muaro Jambi. Participants in this research consisted of all 47 teachers at the school, with data collected through questionnaires and documentation. To ensure the accuracy and precision of analysis, use the SPSS application for data analysis. The findings of this research show that there is a significant relationship between the principal’s leadership style and organizational culture, as evidenced by the correlation coefficient and significance value (sig) of less than 0.05. The t test further confirms the significance of the coefficient thereby providing further evidence of a significant relationship between the principal’s leadership style and organizational culture at SMA Negeri 3 Muaro Jambi. In conclusion, this research emphasizes the important and noteworthy role of leadership style in shaping organizational culture. The uniqueness of this research lies in confirming the influence of leadership style on organizational culture at SMA 3 Muaro Jambi, thereby contributing to a deeper understanding in the educational institutional context